A Comparison of Infrared and Hot Blade Beak Trimming in Laying Hens - Dennis, Rachel L.; Cheng, Heng W. (International Journal of Poultry Science, 2010)
Commercial egg laying farms are under intense pressure to eliminate the practice of beak trimming due to the potential for acute and chronic pain to the trimmed birds. However, elimination of beak trimming may have severe implications for animal welfare, as pecking between untrimmed birds can result in body damage that can ultimately lead to cannibalism. Infrared (IR) beak treatment may provide an alternative solution to the conventional Hot Blade (HB) beak trimming, with the potential for being a more welfare friendly means of reducing procedure-associated tissue injuries. In the present study we followed a flock of production hens from 5 to 35 weeks of age, in which a portion of the flock was trimmed with the IR method and the remaining birds with conventional HB. Thirty birds from each beak treatment were randomly selected for this study. Results showed that IR birds had significantly longer upper and lower beaks throughout the study. The frequency of beaks in which the lower beak was longer than the upper was greater in HB treated birds (10.48% in HB versus 7.62% in IR) and scar tissue was only evident on two birds from the HB treatment and no birds from IR. Behavior analysis showed that IR birds spent less time feeding compared with HB hens; however, these birds were consistently heavier than their HB counterparts, suggesting that IR beak treatment may allow for more efficient feeding behavior. The data suggest that IR beak treatment presents an useful alternative to traditional HB beak trimming.